Investigations Into the Suitability of Bacterial Suspensions as Biological Indicators for Low-Energy Electron Irradiation - Schopf, Simone; Gotzmann, Gaby; Dietze, Marleen; Gerschke, Stephanie; Kenner, Lysann; König, Ulla (Frontiers in Immunology, 2022)
Low-energy electron irradiation is an emerging alternative technology for attenuated or complete pathogen inactivation with respect to medical, biotechnological, and pharmaceutical applications. Pathogen inactivation by ionizing radiation depends mainly on the absorbed electron dose. In low-energy electron irradiation processes, determination of the absorbed electron dose is challenging due to the limited, material-dependent penetration depth of the accelerated electrons into the matter. In general, there are established dosimetry systems to evaluate the absorbed dose under dry irradiation conditions. However, there is no system for precise dose monitoring of low-energy irradiation processes in liquids or suspensions so far. Therefore, in this study three different bacterial species were investigated as biological dose indicators, especially in the range of low doses (< 6.5 kGy) in aqueous solutions or suspensions. Escherichia coli, Bacillus subtilis, and Staphylococcus warneri were comparatively evaluated for their suitability as biological dose indicators. Thin homogeneous films of the respective bacterial suspensions were irradiated with increasing doses of low-energy accelerated electrons. The average absorbed dose was determined using a colorimetric dosimeter based on a tetrazolium salt solution. The maximum and minimum absorbed doses were measured with a referenced film dosimeter. Subsequently, the inactivation kinetics was determined in terms of inactivation curves and D10 values. Thus, the minimum inactivation dose of bacterial growth was assessed for E. coli and S. warneri. The effect of irradiation with low-energy accelerated electrons on the growth behavior and activity of the bacteria was studied in more detail using impedance spectroscopy. With increasing irradiation doses growth was delayed.